Comparison of 3D Maximum intensity projection (MIP) reconstruction and 2D T2 Half-Fourier Acquisition Single-Shot Turbo Spin-Echo (HASTE) sequence in magnetic resonance cholangiopancreatography (Journal of Health Sciences, 2014)
Introduction: Magnetic resonance cholangiopancreatography (MRCP) is a method that allows noninvasive visualization of pancreatobiliary tree and does not require contrast application. It is a modern method based on heavily T2-weighted imaging (hydrography), which uses bile and pancreatic secretions as a natural contrast medium. Certain weaknesses in quality of demonstration of pancreatobiliary tract can be observed in addition to its good characteristics. Our aim was to compare the 3D Maximum intensity projection (MIP) reconstruction and 2D T2 Half-Fourier Acquisition Single-Shot Turbo Spin-Echo (HASTE) sequence in magnetic resonance cholangiopancreatography.Methods: During the period of one year 51 patients underwent MRCP on 3T „Trio“ system. Patients of different sex and age structure were included, both outpatient and hospitalized. 3D MIP reconstruction and 2D T2 haste sequence were used according to standard scanning protocols.Results: There were 45.1% (n= 23) male and 54.9% (n=28) female patients, age range from 17 to 81 years. 2D T2 haste sequence was more susceptible to respiratory artifacts presence in 64% patients, compared to 3D MIP reconstruction with standard error (0.09), result significance indication (p=0.129) and confidence interval (0.46 to 0.81). 2D T2 haste sequences is more sensitive and superior for pancreatic duct demonstration compared to 3D MIP reconstruction with standard error (0.07), result significance indication (p=0.01) and confidence interval (0.59 to 0.87)Conclusion: In order to make qualitative demonstration and analysis of hepatobiliary and pancreatic system on MR, both 2D T2 haste sequence in transversal plane and 3D MIP reconstruction are required.